Violencia intrafamiliar y su incidencia en el rendimiento escolar de los estudiantes del cuarto año de educación general básica de la Unidad Educativa Ecuador, de la parroquia San Carlos, cantón Quevedo - Cedeño Granda, Meredith Linette (2018)
The present investigation has been developed with the objective of analyzing how domestic violence affects the school performance of the students of the Fourth Year of Basic General Education of the Educational Unit "Ecuador" of the San Carlos Parish, Quevedo Canton, Province from the rivers. For the execution of this research, some methodological tools were used, such as field and descriptive research, as well as descriptive, analytical and deductive methods. In addition, techniques such as observation, surveys and interviews were applied to the selected sample in order to gather all the information that interested the investigation. The sample consisted of 16 students, 16 parents, 1 Teacher and the Director of the institution. After the application of the research instruments, the respective tables and statistical graphs showing the results were prepared. The use of the methods, techniques, and suitable instruments allowed the analysis and relationship of the variables studied, and the verification of the hypotheses raised in the research process. At the end of the investigation, it was concluded that there is evidence of some degree of violence within the homes of some of the students, and whose performance does not meet or does not meet the requested requirements. In short, a relationship was found between both variables and a wide acceptance for the proposal of this research.